Wychowanie obywatelskie w jezuickich kolegiach szlacheckich... - Puchowski, Kazimierz (Horyzonty Wychowania, 2017)
In his article, K. Puchowski takes up the problem of civic educationin Jesuit colleges for nobility in the First Republic of Poland.Establishing colleges was supposed to be the reaction ofJesuits, Piarists, and Theatines to the expectations of the state,which wanted to have well-prepared elites in order to introducereforms necessary at that time. The author makes a brief comparisonand analysis of the activity of colleges for nobility run byindividual orders, with special attention paid to Jesuit colleges.Jesuit colleges in the Republic of Poland aimed at training exemplarycitizens, full of religiousness and patriotism. The authordisagrees with the standpoint, expressed in literature, that educationin colleges for nobility was deprived of civic character,which he attempts to prove in the article, showing various formsand methods of shaping civic attitudes. Colleges passed on notonly knowledge, but they also shaped the attitudes of respectfor statehood. Jesuit schools were elitist, different from knights’schools of the time. The teaching staff was well-prepared forconducting cultural and political education. They trained the sonsof the well-known Polish noblemen cherishing hope that it wouldprove useful in the process of restoring the Republic of Poland.K. Puchowski enumerates the leading figures for the area underdiscussion, such as: Karol Wyrwicz, Franciszek Bohomolec,Adam Naruszewicz and others, who had influence on the shapeof the colleges for nobility in the Crown and Lithuania. Thosepeople were characterised by a critical approach towards whatwas happening in the Republic of Poland and willingness to educateenlightened citizens for the Homeland.